Thermodynamic characterization of mixed gas hydrates in the presence of cyclopentane as guest molecule for an application in secondary refrigeration. (23rd November 2021) - Chami, Nada; Bendjenni, Sabrina; Clain, Pascal; Osswald, Véronique; Delahaye, Anthony; Fournaison, Laurence; Dalmazzone, Didier
Highlights: Phase equilibria of mixed c-C5 H10  + CO2 hydrates were presented. Dissociation enthalpies of mixed c-C5 H10  + CO2 hydrates were measured by µDSC and calculated using Clausius-Clapeyron method. The composition of mixed c-C5 H10  + CO2 hydrates formed in the system was calculated. The heat capacity of mixed c-C5 H10  + CO2 hydrates was measured in the temperature range 277.9 K to 281.2 K. Abstract: Gas hydrates have drawn the attention of many scientists because of their potential role in energy applications. By using some thermodynamic promoters, it is possible to form hydrates at reduced pressure and near ambient temperature, which are suitable formation conditions for most industries. In this study, a high pressure micro differential scanning calorimeter was used to measure the dissociation conditions of mixed cyclopentane (c-C5 H10 ) + CO2 hydrates in the system composed of liquid water + liquid hydrocarbon + hydrate + vapour, in a pressure range of 0 to 4.3 MPa in a temperature range of 280 to 292 K. The analysis of the heat flow curve allowed the direct determination of the dissociation enthalpy of c-C5 H10  + CO2 hydrates (e.g., Δ H = 462.5 ± 1.5 kJ. kg −1 water at equilibrium pressure 0.25 MPa) and the average mass heat capacity of c-C5 H10  + CO2 hydrates in a temperature range of 277.9 - 281.2 K (CpH  = 1479.09 ± 137.43 J. K −1 . kg −1 hydrate at 0.25 MPa).